2016
DOI: 10.1186/s12893-016-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

Psoas abscess secondary to retroperitoneal distant metastases from squamous cell carcinoma of the cervix with thrombosis of the inferior vena cava and duodenal infiltration treated by Whipple procedure: A case report and review of the literature

Abstract: BackgroundPsoas abscess is a rare clinical disease of various origins. Most common causes include hematogenous spread of bacteria from a different primary source, spondylodiscitis or perforated intestinal organs. But rarely some abscesses are related to malignant metastatic disease.Case presentationIn this case report we present the case of a patient with known squamous cell carcinoma of the cervix treated with radio-chemotherapy three years prior. She now presented with a psoas abscess and subsequent complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Of the 15 cases reported identifying metastatic spread to the bowel [1,[3][4][5][6][7][8][9][10][11][12], three presented with upper gastrointestinal bleeding [1,3], one with small bowel perforation [3], one with a psoas abscess [12], one incidentally [11], and the rest with obstructive symptoms or pain [3][4][5][6][7][8][9][10]. The most common site within the small bowel tends to be the duodenum [1,[3][4][5][6][7][8][9]11] with three cases in the ileum [1] and two in the jejunum [1,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 15 cases reported identifying metastatic spread to the bowel [1,[3][4][5][6][7][8][9][10][11][12], three presented with upper gastrointestinal bleeding [1,3], one with small bowel perforation [3], one with a psoas abscess [12], one incidentally [11], and the rest with obstructive symptoms or pain [3][4][5][6][7][8][9][10]. The most common site within the small bowel tends to be the duodenum [1,[3][4][5][6][7][8][9]11] with three cases in the ileum [1] and two in the jejunum [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…The most common site within the small bowel tends to be the duodenum [1,[3][4][5][6][7][8][9]11] with three cases in the ileum [1] and two in the jejunum [1,10]. Indirect small bowel obstruction via para-aortic lymph nodes caused by cervical metastases has also been reported [3,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several patients positive for human immunodeficiency virus (HIV) have been reported to have psoas muscle metastasis, most frequently from cervical cancer [6]. Some cases of cervical cancer in HIV-negative patients also have been reported [7][8][9][10]; however, only one case of psoas muscle metastasis from endometrial cancer has been reported [1]. Hematogenous, lymphatic and disseminated spread has been considered as pathways for skeletal muscle metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, malignant carcinoma mimicked a psoas abscess and presented with the typical symptoms. Neoplasms like cervical [1], colorectal [2], renal cell [3], and lung carcinomas [4] have been reported to present as psoas abscess.…”
mentioning
confidence: 99%